Advances in the Relationship Between Regulator of Ribosome Synthesis 1 (RRS1) and Diseases - Hua, Yanan; Song, Jinlian; Peng, Cuixiu; Wang, Runze; Ma, Zhongliang; Zhang, Jinyu; Zhang, Zheng; Li, Ning; Hou, Lin (Frontiers in Cell and Developmental Biology, 2021)
Regulator of ribosome synthesis 1 (RRS1) was first discovered in yeast in 1999. RRS1 is the regulation of the synthesis of ribosomal protein, RRS1 protein was mainly localized in the nucleolus and endoplasmic reticulum, RRS1 was found in yeast, and it was related with protein secretion pathway and ribosomal rRNA messenger and ribosomal protein synthesis. RRS1 takes part in the biosynthesis of ribosomal subunit, and it plays an important role in ribosome synthesis, and it has some extra ribosomal functions, including participation in cell senescence, cell cycle regulation, transcription and translation regulation, and cell malignant transformation etc. The abnormality of RRS1 gene plays an important role in the occurrence and development of Huntington's disease and cancer, the over expression of RRS1 gene can promote the proliferation and metastasis of tumor. In this paper, the structure, function, mechanism of RRS1 and the related research progress in disease were reviewed.